(untitled) (Journal of Academic Research, 2026)
This qualitative case study examines patterns of student silence and spoken response in second-year EFL classes at the Faculty of Education, Elmergib University, Al-Khums. Data were collected during March and April 2023 through classroom observation of ten lectures, semi-structured interviews with three lecturers, and a short supporting written student survey. Thematic analysis identified four main patterns: spoken responses were limited and unevenly distributed across sessions; lecturers used Arabic and translation regularly to maintain comprehension and lesson flow; lecturers responded to hesitation in different ways, and this appeared connected with whether students attempted spoken responses; and participation appeared connected with students’ confidence, preparation habits, vocabulary anxiety, and assessment expectations. The findings suggest that limited spoken response in this setting cannot be explained by language level alone. It is connected with classroom habits, teacher questioning patterns, the role of Arabic support, and students’ perception that speaking carried limited weight in formal assessment. The paper offers practical suggestions for lecturers working in similar EFL settings.